Pengaruh Keterampilan Membaca Pemahaman Terhadap Kemampuan Pemecahan Soal Cerita Matematika Kelas V Madrasah Ibtidaiyah Al-Zaytun - Siarnagama, Lega; Peranginangin, Henri; Rahim, Abdur (JUPE : Jurnal Pendidikan Mandala, 2023)
This thesis examines the effect of reading comprehension skills on the ability to solve math story problems in class V Madrasah Ibtidaiyah Ma'had Al-Zaytun. The first problem is that not all of the fifth grade students have good reading comprehension skills. The second main problem is that there are still many students who have difficulty understanding word problems, especially word problems in mathematics. This study aims to determine the effect of reading comprehension skills on the ability to solve math story problems in class V of Madrasah Ibtidaiyah Al-Zaytun. This type of research is ex post-facto research. The population of this study were all students of class V MI Al-Zaytun totaling 241 students. There were 150 research samples who were randomly selected using the Simple Random Sampling technique. The variables studied were reading comprehension skills (Variable X) and ability to solve math word problems (Variable Y). Data collection techniques in this study used test instruments that had been tested for validity and reliability. Hypothesis testing uses simple regression analysis with the help of the SPSS version 24 program. The results of the research were processed using a simple regression test showing that reading comprehension skills had a significant effect on the ability to solve math word problems. This was indicated by a sig value of less than 0.05, which is equal to 0.000 with the regression equation y = 2.396 + 0.874x. So the hypothesis is accepted that there is a significant effect between reading comprehension skills on the ability to solve math story problems for class V MI Al-Zaytun in the 2020/2021 academic year.